2012
DOI: 10.1038/hr.2011.217
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial migration by fibroblast progenitor cells is blood pressure dependent in a model of angII myocardial fibrosis

Abstract: Activation of the renin-angiotensin system (RAS) is thought to promote myocardial fibrosis. However, it is unclear whether this physiological fibrotic response results from chronic hemodynamic stress or from direct cellular signaling. Male C57B/6 mice were randomly assigned to receive angiotensin II (AngII) (2.0 lg kg À1 min À1 ), AngII+hydralazine (6.9 lg kg À1 min À1 ) or saline (control) via osmotic pumps for 7 days. Blood pressure was measured via noninvasive plethysmography. Hearts were harvested and proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(67 reference statements)
2
8
0
Order By: Relevance
“…Our additional observation that combination led to no greater reductions in fibrosis suggest that mechanism to promote fibroblasts in this model are more dependent on hemodynamic that hormonal factors, per se. Thereby, our findings are contrary to the premise that greater reductions in aldosterone would then lead to greater reductions in fibrosis in this transgenic model and corroborate recent work in Ang II infused mice suggesting that fibroblast migration and interstitial fibrosis may be pressor-dependent processes[42]. …”
Section: Discussionsupporting
confidence: 75%
“…Our additional observation that combination led to no greater reductions in fibrosis suggest that mechanism to promote fibroblasts in this model are more dependent on hemodynamic that hormonal factors, per se. Thereby, our findings are contrary to the premise that greater reductions in aldosterone would then lead to greater reductions in fibrosis in this transgenic model and corroborate recent work in Ang II infused mice suggesting that fibroblast migration and interstitial fibrosis may be pressor-dependent processes[42]. …”
Section: Discussionsupporting
confidence: 75%
“…In the wellestablished AngII-dependent model of hypertension, we and others have demonstrated an absence of tissue necrosis and associated polymorphonuclear cell infiltrates, suggesting that this model may not require the mass influx of classical macrophages. 7,15,16,21,23 We have also characterized that early myocardial infiltration in AngII-exposed hearts is largely unaffected in Ccr2 À/À mice, suggesting redundancy in chemokines or implicating Cx3cr1-dependent nonclassical macrophage recruitment. 21 Despite this body of evidence it remained to be demonstrated whether macrophages were mediating the cellular changes observed in the myocardium and the ECM remodeling after AngII infusion.…”
Section: Discussionmentioning
confidence: 94%
“…Mice were randomly assigned to either saline (vehicle) or Ang-II (2.8 mg/kg/d; Sigma-Aldrich, Oakville, ON, Canada) through the use of subcutaneously implanted Alzet osmotic minipumps (Alzet Corp., Palo Alto, CA) as previously described. 21 , 22 In brief, isoflurane with oxygen was used to anesthetize mice. A mid-scapular skin incision (approximately 1–2 cm) was made to implant the osmotic minipump subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
“…In animal models, our group has focused our attention on the initial few days post-angiotensin II (Ang-II) infusion and demonstrated that significant inflammation and fibrosis development were associated with increased expression of TGF-β and CTGF in the myocardium. 18 , 21 23 Highlighting the importance of time-dependent events leading up to fibrosis, our previous work also demonstrated a marked elevation in CTGF gene expression prior to significant TGF-β production that remains to be fully characterized. 18 …”
Section: Introductionmentioning
confidence: 95%